CELEBRATING STUDENTS' DIVERSITIES THROUGH UNDERSTANDING STUDENTS' CHARACTERISTICS - Desi Antri Astuti; Endang Fauziati; Sri Marmanto (Informascope, 2019)
Dealing with different students' characteristics cannot be avoided by the teacher in everyday teaching. It is well-known that teaching English to young learners is different from teaching an adult. Therefore, teachers are required to understand the characteristics of the students in order to know the students' needs so that learning goals can be achieved effectively. Research under the case study design had been done at a private school in Surakarta which used interview and observation to collect the data from 2 English teachers in that school. This research aims at investigating the teachers' beliefs on understanding characteristics of students and exploring how those beliefs are reflected in the teaching-learning practices. The result shows the two participants believe that understanding the characteristics of students is important for teachers because it can help them to develop their teaching-learning strategy and achieve learning objectives effectively. This research also reveals the way the participants reflect their beliefs in teaching-learning practices. Keywords: beliefs, students' characteristics, young learners, teaching English